Implementation of E-Government in the Online Motor Vehicle Tax Collection System (E-Samsat) in the Regional Technical Implementation Unit of the One-Stop Single Administration System in Binjai City, North Sumatra Province - Nindya Adhisty; Muhadam Labolo; Yudi Rusfiana (Sean Institute, 2024)
This research is motivated by the people of Binjai city still not understanding the use of the e-Samsat application. This research aims to analyze and determine the implementation of E-Government in the online motor vehicle tax collection system (e-samsat) in the regional technical implementation unit of the one-stop single administration system in Binjai City, North Sumatra Province. This research uses descriptive qualitative methods. The data sources used are primary data and secondary data. data collection techniques through observation, interviews and documentation. data analysis method with data reduction, data presentation and drawing conclusions. The results of this research show that the implementation of E-government in the online motor vehicle tax collection system (E-samsat) at the Binjai City Samsat UPTD. In terms of interpretation and organization indicators, implementation of the motor vehicle tax collection system is still not optimal. Meanwhile, the only indicator that shows that the implementation of the motor vehicle tax collection system through the e-Samsat application is quite good is the implementation indicator. Then there is a need for Binjai City Samsat to be more optimal and quick to respond to problems that are obstacles, namely by increasing the competency of human resources by carrying out special training related to managing the E-Samsat application so that the goals to be achieved are realized. Then respond more optimally and quickly to problems with the E-Samsat application server connectivity system by increasing the budget to increase server power so that the motor vehicle tax collection system process through the E-Samsat application, especially in Binjai City, runs effectively.